Report on the development of the national method for the assessment of ecological status of natural lakes in Greece, with the use of littoral benthic invertebrates - Mavromati, E.; Κεμιτζόγλου, Δήμητρα; Tsiaoussi, V.; M. Lazaridou (Ministry of Environment and Energy. Special Secretariat for the Natural Environment and Waters, 2021)
This report discusses the development of a national method for the assessment of ecological status of natural lakes in Greece, based on the Biological Quality Element (BQE) “Benthic Invertabrate Fauna” from the littoral zone, the Hellenic assessment method for Lake Littoral Benthic invertebrate fauna (HeLLBI). Most lake assessment methods based on benthic macroinvertebrates to date, evaluate eutrophication and acidification; fewer methods assess morphological pressures on lake ecosystems and they are mostly based on benthic macroinvertebrates from the littoral zone (Poikane et al., 2016). Greece has a national method for zoobenthos from the profundal zone (GLBiI - Greek Lake Benthic invertebrate Index), that addresses eutrophication, which is included in the 2018 Intercalibration Decision [Commission Decision (EU) 2018/229] (Ntislidou et al., 2018). The development of the current assessment method, as described in this report, is based on data from the national water monitoring network. In particular, 109 littoral sampling sites in 21 lakes (29 lake years) have been surveyed for benthic invertebrates during the 2015-2018 sampling campaign. Natural lakes in Greece are grouped into 3 types, according to the mixing regime and depth gradient1. As the sampling took place in the littoral zone, data from all lake types were pooled in the dataset. The HeLLBI method consists of metrics indicative of taxonomic composition and abundance, sensitivity/tolerance of taxa and taxa diversity. It addresses morphological alteration and eutrophication pressures.